Impact of Goods and Services Tax on Micro, Small and Medium Enterprises - Dr. Usha (International Journal of Engineering and Management Research, 2024)
In the present scenario Micro, Small, and Medium Enterprises face several challenges. One of the changes in the Indirect Tax regime was the implementation of the Goods and Services Tax. The changes in Goods and Services Tax regime laws and rules bring another challenge to the Micro, Small, and Medium Scale Sector. To find out the impact on various aspects such as applying of Goods and Services Tax, created the registration for taxation and high compliance burden by using random sampling technique in which 78 MSME entrepreneurs were selected in Udupi District of Karnataka State. The data required for this study is collected through both primary and secondary sources. The purpose of this study is to analyze the impact of goods and services tax on the MSMEs sector. It was concluded that the impact of Goods and Services Tax on the Micro, Small, and Medium Scale sector can go both positive and negative ways.